Political brain in electoral processes: the emotions of the vote in the 2018 Presidential Campaign in Mexico (2019)
The electoral processes in Mexico during the 21st century have been characterized by a high level of uncertainty regarding the motivations and conditions in which citizens cast their vote. The role played by emotions when casting the vote that will determine the direction of an election day is becoming more evident. The purpose of this research was to identify the role of emotions in the political-electoral definition for the 2018 Mexican elections, in order to demonstrate that it is an emotional choice, rather than a rational one, what shapes Mexico’s emotional public space and its governance. To achieve this purpose, a qualitative methodological approach was used, because the discursive strategies used by one of the candidates competing for the presidency of the Mexican Republic, Andrés Manuel López Obrador, who was leading the polls and eventually won the elections, was analyzed. Among the most significant findings of the investigation, it was found that Andrés Manuel López Obrador has known how to take advantage of an emotional public space of irritation and social anger, in order to give rise to a kind of emotional governance. Recent studies in the field of neuroscience show that the decisions made by human beings are not only a product of reason, but that emotions triggered by the media and social networks, among others, have a defining role in them.